Degradation Behaviors of Two Epoxy Coatings After Dry/Wet-Accelerated Fog Exposure of Different Solutions - Zhang, Jibiao; Zhu, Bo; Wang, Haoran; Zhang, Cheng; Zeng, Weixiu; Zhou, Qixin (Frontiers in Materials, 2021)
Applying organic coating is an important and effective approach for the protection of metal from corrosion. Weathering degradation and under-film corrosion are the two major important factors that cause the failure of organic coatings. In this work, the degradation investigation of two epoxy coatings (clear and pigmented coatings) was carried out under the dry–wet circulation of three different water fog solutions (deionized water, 0.5 wt% NaCl, 0.05 wt% NaCl + 0.35 wt% (NH4)2SO4) in 35 days. The apparent performance (pull-off adhesion and surface potentials) and electrochemical features [electrochemical noise and electrochemical impedance spectroscopy (EIS)] of the coating samples were monitored after dry–wet fog exposure. In our three accelerating systems of the fog atmosphere, the time that the detectable defects appeared on the surface of coating samples was far ahead in the mixed salt solution than that in the deionized water or 0.5 wt% NaCl solution. For a defective or damaged coating surface, the derived results by using the standard deviation method (SDM) or Fourier power spectrum (FPS) were rather higher than those obtained from EIS as a whole, while for the same coating, the degradation trend with time derived from EIS, SDM, FPS, and scanning Kelvin probe was consistent with each other.